Flavonoids from Hibiscus sabdariffa reduce serum aldosterone level of hypertensive male Wistar rats - Somke P Madueke; Daniel C Nwachukwu; Ruku Ubom; Oluchi Okafor; Okwute M Ochayi; Obianuju I Ojikah; David C Ikwuka; Uchenna Katchy (International Journal of Medicine and Health Development, 2024)
Background: Flavonoids are associated with a broad spectrum of health-promoting effects and are an indispensable component in a variety of nutraceutical, pharmaceutical, medicinal, and cosmetic applications. Objectives: This study was aimed to investigate the effect of flavonoids from Hibiscus sabdariffa on the aldosterone level of hypertensive male Wistar rats. Materials and Methods: Thirty-five male Wistar rats were divided into seven groups (n = 5) and allowed access to feed and water for 2 weeks. Salt loading was used to induce hypertension. Different concentrations of flavonoids were administered to three of the experimental groups at 50, 100, and 200 mg/kg, respectively. Lisinopril at 30 mg/kg was administered to positive control whereas Group 7 had co-administration lisinopril (30 mg/kg) and flavonoids (200 mg/kg). The rats in the control group were given just feeds and water. The experiment lasted for 4 weeks. Serum aldosterone was measured using radioimmunoassay kits. Results: The result showed that the mean values of serum aldosterone decreased significantly (P < 0.05) when compared with its baseline value. Blood pressure also reduced. Conclusion: This work has shown that flavonoids from H. sabdariffa may have relevant anti-hypertensive effects bordered on reduction in serum aldosterone level and regulation of serum electrolyte balance.